A Genetic Screen and Transcript Profiling Reveal a Shared Regulatory Program for Drosophila Linker Histone H1 and Chromatin Remodeler CHD1. - Kavi, H.; Lu, X.; Xu, N.; Bartholdy, B.A.; Vershilova, E.; Skoultchi, A.I.; Fyodorov, D.V. (G3 : genes - genomes - genetics, 2015)
Chromatin structure and activity can be modified through ATP-dependent repositioning of nucleosomes and posttranslational modifications of core histone tails within nucleosome core particles and by deposition of linker histones into the oligonucleosome fiber. The linker histone H1 is essential in metazoans. It has a profound effect on organization of chromatin into higher-order structures and on recruitment of histone-modifying enzymes to chromatin. Here, we describe a genetic screen for modifiers of the lethal phenotype caused by depletion of H1 in Drosophila melanogaster. We identify 41 mis-expression alleles that enhance and 20 that suppress the effect of His1 depletion in vivo. Most of them are important for chromosome organization, transcriptional regulation, and cell signaling. Specifically, the reduced viability of H1-depleted animals is strongly suppressed by ubiquitous mis-expression of the ATP-dependent chromatin remodeling enzyme CHD1. Comparison of transcript profiles in H1-depleted and Chd1 null mutant larvae revealed that H1 and CHD1 have common transcriptional regulatory programs in vivo. H1 and CHD1 share roles in repression of numerous developmentally regulated and extracellular stimulus-responsive transcripts, including immunity-related and stress response-related genes. Thus, linker histone H1 participates in various regulatory programs in chromatin to alter gene expression.